Relationships between transpiration, water loss, and air conditions during physiological drying. Issue 2 (25th January 2018) - Wang, Zhe; Zhou, Zhi-xin; Wang, Xi-ming; Chen, Zhang-jing
ABSTRACT: Tree transpiration can cause a rapid decrease in the moisture of tree trunk after felling. In this study, the physiological drying of poplar logs was examined as a result of transpiration. Experiments were conducted on poplar trees with and without canopies and where the water supply from the roots was blocked. The effect of transpiration on the drying process and the relationships between transpiration, water loss, and air conditions were investigated. Statistical analysis of the data showed that the moisture content (MC) decreased significantly as a result of physiological drying at a rate of 5.65% MC/day within 3 days, 3.85% MC/day within 5 days, and 2.30 MC/day within 9 days. The transpiration rate of the trees was positively correlated with the moisture loss. Leaf transpiration of control trees and those where access to water was blocked was strongly and similarly affected by air conditions, although the water-blocked treatment resulted in a significantly lower transpiration rate. The transpiration rate and stomatal conductance increased as relative humidity increased and as vapor pressure deficit decreased. When transpiration-mediated water loss occurred, the temperature difference between the air and leaf surface was approximately 1–3°C. The results indicate that transpiration is the main driving force that reduces water during physiological drying, and the main factors that influence this process are the air conditions.